Analysis of Optimization of Fixed Asset Management for Sleman Regency Government - Linda Vebriana; Rifki Khoirudin; Fatima Muhammad Abdulkarim (Universitas Ahmad Dahlan, Yogyakarta, 2022)
The key to successful economic management is related to the management of regional assets. Optimal management of regional assets will prioritize good governance and trustworthy management of state finances from the community. However, there are still some problems that occur in the management of fixed assets in the Sleman Regency Government. This research is a quantitative descriptive study that explains the relationship between asset inventory, valuation, legal audit, and supervision and control of the optimization of fixed assets. Research data was collected through the distribution of questionnaires. The analytical tool used is multiple regression analysis. The results showed that the inventory, assessment and supervision and control had an effect on the optimization of fixed assets. While the legal audit has no effect on the optimization of fixed assets.